Hopkins’s Sermons and “Felix Randal” - Marshall, Elaine F. (Religion and the arts, 2015)
Since Alfred Thomas’s discovery in 1971 that Hopkins had entered the death of his parishioner, Felix Spencer, in St. Francis Xavier’s church record book, scholars have interpreted Hopkins’s sonnet, “Felix Randal,” in the context of his ministerial experience in Victorian Liverpool. This paper aims to add to existing research on “Felix Randal” by analyzing some of the sonnet’s underlying themes in the light of Hopkins’s Bedford Leigh and Liverpool sermons, and sources on Felix Spencer and his environment that have not yet received attention by critics. These sources include The Gore’s Directory, contemporary newspapers, and material on Felix Spencer’s burial. The investigation will reveal that, despite the differences between Hopkins’s sermons and “Felix Randal,” some of the teachings in his sermons, together with information on the social conditions in his urban parishes, can help the reader to probe the obscurities in the sonnet, and offer additional interpretations of its meaning.